Miliary Tuberculosis in Children: A Clinical Review - Rahajoe, Nastiti N. (Indonesian Pediatric Society, 1990)
Eighty cases of miliary tuberculosis admitted to our hospital between January 1981 and December 1984 were reviewed. The age of the patients ranged from 3 months to 12 years, with an average of 2 years 2 months (26.5 months). Nine cases (11.25%) died during hospitalization due to the severe condition at the time of admission. Only 8 patients (10%) were in good nutritional condition. Seventy-two patients (90%) had been visiting the primary health care clinic for several times since 2-3 months but were never diagnosed as suffering from tuberculosis. Fever or recurrent fever were found in 78 cases (97.5 %o), anorexia in 65 cases (81.3 %), chronic and/or recurrent cough in 72 cases (90%) and malaise in 43 (53.8%). Forty-one (51.3%) denied the presence of a close contact with source of infection. Hepatomegaly was found in 44 cases (55%), 19 (23.8%) of which were associated with splenomegaly. Choroidal tubercle was found in 4 cases; 1 case with coxitis, 1 with brain tuberculoma, 1 with ascites, 1 with endobronchitis and 1 with hepatitis. Forty-three (53.8%) were tuberculin negatives, 24 of which become positives after treatment. Fourteen cases had BCG scar. History of measles was found in 21 cases. Children with long-term and recurrent fever, anorexia, decrease in body weight, and recurrent cough should be suspected of having TB, thus enabling to get an early diagnosis.